Finding best urban routes based on analyses of high level and IOPT Petri net models - Dezani, Henrique; Gomes, Luis; Damiani, Furio; Marranghello, Norian [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
This paper presents a tool that combines two kinds of Petri Net analyses to set the fastest routes to one vehicle in a bounded area of traffic urban. The first analysis consists of the discovery of possible routes in a state space generated from an IOPT Petri net model given the initial marking as the vehicle position. The second analysis receives the routes found in the first analysis and calculates the state equations at incidence matrix created from the High Level Petri net model to define the fastest route for each vehicle that arrive in the roads. It was considered the exchange of information between vehicle and infrastructure (V2I) to get the position and speed of all vehicles and support the analyses. With the results obtained we conclude that is possible optimizing the urban traffic flow if this tool is applied to all vehicles in a bounded urban traffic. © 2012 IEEE.
Keywords: Exchange of information; Fastest route; Incidence matrices; Initial marking; Petri net models; State equations; State space; Urban traffic; Urban traffic flow; Vehicle position; Industrial electronics; Petri nets; Vehicles